Aplikasi Diagnosa Granulomatous Dermatis Menggunakan Certainty Factor - Puji Sari Ramadhan (STMIK Budi Darma, 2019)
Granulomatous dermatitis is a type of inflammatory disease in the inner layer of the skin that causes damage to the nerves, skin layers and motor members of the body. This disease originated in the attack of an aerobic type of mycobacterium leprae which can spread and transmit infection by contact and air, besides this disease is estimated to enter Indonesia in the early V century. At present the diagnosis and treatment of Granulomatous Dermatis is experiencing difficulties, this based on the limited information and lack of knowledge of the community about Granulomatous Dermatis so that later it will result in late or unpreparedness of treatment in patients with Granulomatous Dermatis cases. On the basis of these events, it is very necessary to build a system by acquiring scientific concepts of artificial intelligence that are capable of producing an Expert System which can later be used to diagnose Granulomatous Dermatis by applying the Certainty Factor analysis. With the application of this diagnosis later can help the community and medical experts in diagnosing Granulomatous Dermatis as a reference tool in concluding the final diagnosis.